Retinal Microvasculature Is Associated With Long-Term Survival in the General Adult Dutch Population. Issue 2 (February 2016) - Mutlu, Unal; Ikram, M. Kamran; Wolters, Frank J.; Hofman, Albert; Klaver, Caroline C.W.; Ikram, M. Arfan
Abstract : Retinal vascular diameters are associated with (sub)clinical cardiovascular disease and short-term cardiovascular mortality, but their association with long-term mortality is uncertain. We studied the association of retinal vascular diameters with cause-specific mortality in the general adult Dutch population during 25 years of follow-up. From 1990 to 1993, arteriolar and venular diameters were measured semiautomatically on digitized images in 5674 persons (mean age 68.0 years, 59% women) from the population-based Rotterdam study. Follow-up for mortality was complete till March 2015. Associations between vascular diameters and mortality were examined using Cox proportional hazards models, adjusting for age, sex, cardiovascular risk factors, and the fellow vessel diameter. During 85 770 person-years (mean±SD: 15.1±6.67), 3794 (66.8%) persons died, of whom 1034 due to cardiovascular causes. We found that narrower arterioles and wider venules were associated with higher risk of mortality (adjusted hazard ratio [95% confidence interval] per SD decrease 1.04 [1.00–1.08] and increase 1.07 [1.03–1.12], respectively). For arterioles, these associations were strongest for cardiovascular mortality, whereas venules showed consistent associations for cardiovascular and noncardiovascular mortality. Importantly, these associations remained unchanged after excluding the first 10 years of follow-up as immortal person-time. We found evidence for effect modification with stronger associations in persons <70 years (venules only) and smokers ( P value for interaction<0.01). We replicated our findings in another independent cohort from the Rotterdam Study of 3106 persons with 19 880 person-years of follow-up and 144 deaths (hazard ratio for venules 1.22 [1.00–1.49]). Markers of retinal microvasculature are associated with long-term mortality in the general adult Dutch population. Abstract : Supplemental Digital Content is available in the text.